Enhancing caregiving for older adults: meeting basic needs and overcoming challenges in e-homecare - Rochmawati, Erna; Setyonugroho, Winny; Islami, Moch Zihad; Lestari, Tri; Khanif, Akhmad (International Journal of Public Health Science (IJPHS), 2024)
Ensuring proper care for older adults in their homes is becoming increasingly important as the older adult population grows. This paper investigates caregivers' perspectives regarding their care for older adults and their acceptance of e-homecare technology. This is a qualitative study with data collection through interviews with five caregivers representing a range of qualifications. A thematic analysis was conducted to gain insights into their experiences and preferences. The study reveals three primary findings that contribute to enhancing caregiving for older adults: i) the significance of meeting the basic needs of homecare technology, such as medication administration, vital sign monitoring, and nutrition management; ii) the caregivers' attitudes towards the acceptance and integration of e-homecare technology into their practices; and iii) the challenges faced in implementing and utilizing e-homecare technology effectively. These findings highlight the importance of addressing the fundamental requirements of e-homecare and overcoming the obstacles associated with incorporating technology, ultimately improving the quality of care provided to older adults in their homes.